(untitled) - Davis, R.K. (New york, 1995)
4 Total Productive Maintenance (TPM) is a fundamentally different way of operating manufacturing businesses that can provide considerable benefits in productivity. TPM is a Japanese originated philosophy aimed at maximizing the effectiveness of machinery and equipment on the shop floor. The book provides a way of linking machinery performance directly to business ratios and shows the damage that can be done if operatives and maintence staff do not work together in TPM teams. The book shows how to get to the root cause of low manufacturing performance and morale and how TPM can be applied to make improvements and thereby increase productivity. This work is intended primarily for: professionals in the manufacturing industry involved in production and/or the maintenance of production facilities; manufacturing/operations managers, maintenance managers, facilites managers; and engineering managers. Secondly, it is recommended further reading on manufacturing management courses.
Keywords: Total productive maintenance.,Plant maintenance